Time Outdoors in Nature to Improve Staff Well-Being: Examining Changes in Behaviors and Motivations Among University Staff in the Use of Natural Outdoor Environments Since the Emergence of the COVID-19 Pandemic - Loebach, Janet; Rakow, Donald A.; Meredith, Genevieve; Shepley, Mardelle McCuskey (Frontiers in Psychology, 2022)
Background: Work-related stress is of growing concern to employers because of its significant implications for employee dissatisfaction, reduced productivity, and lowered emotional and physical health. Job-related stress is particularly acute among staff members in higher education, negatively impacting the professional work and personal welfare of staff. During the COVID-19 pandemic, stress levels increased as work expectations and environments shifted, as did new non-work responsibilities, such as care of dependents. We sought to explore if staff were spending more time outdoors in nature during the pandemic (as compared to pre-pandemic times), and whether any increase was intended to achieve some of the well-documented benefits including managing stress, and bolstering mental health and wellbeing. Methods: This study surveyed 507 staff from a large US university to examine the degree to which staff were spending time in NOEs during the pandemic, and whether and how nature-based routines and motivations changed as a result of its emergence. Results: The majority of staff respondents reported spending more time in NOEs since COVID-19 emerged, particularly early on in the pandemic. The most significant change was the increase in time spent outdoors for restorative purposes, including stress relief and improved mental health. Relative accessibility of NOEs, in terms of proximity and number of barriers to access, significantly impacted both time outdoors and the number of NOEs used. Convenient access to NOEs was not experienced equally across staff respondents; barriers to access were higher among staff living with others or dependents, and those who identify as non-White. Conclusions: Spending time outdoors may have served as a protective factor for many staff against some of the detrimental effects of the pandemic. Universities can contribute to the ongoing well-being of staff by supporting access to safe, high-quality NOEs on or near campuses. This provision, along with alternative work arrangements which allow for more time for self-care during the workday, including spending time outdoors in nature, may improve the well-being of staff and reduce disparities in access to nature and experience of its benefits.